IoT-Based Three-Phase Induction Motor Monitoring System - Ridho Syawali; Selamat Meliala (Journal of Renewable Energy, Electrical, and Computer Engineering, 2023)
This paper describes how to use the Internet of Things to control and monitor induction motors. Because it can be utilized from anywhere via Wi-Fi, IoT is more convenient and efficient to control the system. The purpose of this monitoring system is to prevent induction motor failure by implementing preventive measures. Induction motors are used in a variety of applications such as in industry due to their many advantages such as self-starting, high power factor, and rugged design. As a result, using the best available smart protection techniques, it is imperative to detect flaws in the motor at an early stage to improve the efficiency of the motor and ensure safe and reliable operation. The voltage, current and temperature of the induction motor can be monitored remotely with the Blynk IoT application. The monitoring results will determine the error in the motor operating parameters that caused severe damage to the motor. Three PZEM-004T sensors to obtain parameters of each R, S, and T phase of the motor in real-time and relays to control the motor are used in this system to monitor and regulate using IoT. Information from the sensor is received by the microcontroller unit, which processes the sensing data. If an abnormal value is detected, the system automatically generates a control signal to start or stop the motor.